"THE IMPACT OF FOREIGN TRADE ON THE NUMEROUS OF ECONOMIC SECTORS IN IRAQ FOR THE PERIOD (2003–2021)" - SLOW, JASIM AHMED (Journal of Duhok University, 2023)
This study investigates the impact of foreign trade on the components of economic growth in Iraq. Understanding the interdependence of foreign trade and economic growth is of paramount significance for nations striving to foster sustainable development. This study depends on the hypothesis that fluctuations in foreign trade, both imports and exports, significantly impact the performance of key economic sectors—namely agriculture, industry, and services—ultimately shaping Iraq's overall economic growth trajectory. The purpose of this study is to investigate the impact of foreign trade on the components of economic growth in Iraq over the period from 2003 to 2021. To achieve the objectives of this study, an econometric approach known as the Autoregressive Distributed Lag (ARDL) method will be employed. This methodology is well-suited for time series analysis, particularly when dealing with variables that exhibit long-term relationships as well as short-term dynamics. The study found that the impact of foreign trade varies by sector. The agricultural sector has been especially heavily damaged, unable to compete with imported supplies. The industrial sector has been impacted as well, albeit to a lesser level. Because it is less exposed to international competition, the services sector has suffered the least. The main suggestion of this study is the government should provide more support to the agricultural sector, as well as, support its local industries so that it can compete with imported goods.